Caregiver outcomes of the REACH-HF multicentre randomized controlled trial of home-based rehabilitation for heart failure with reduced ejection fraction. (October 2019) - Wingham, Jennifer; Frost, Julia; Britten, Nicky; Greaves, Colin; Abraham, Charles; Warren, Fiona C; Jolly, Kate; Miles, Jackie; Paul, Kevin; Doherty, Patrick J; Singh, Sally; Davies, Russell; et al.
Background: Caregivers frequently provide support to people living with long-term conditions. However, there is paucity of evidence of interventions that support caregivers in their role. Rehabilitation EnAblement in Chronic Heart Failure (REACH-HF) is a novel home-based, health-professional-facilitated, self-management programme for patients with heart failure (HF) and their caregivers. Methods: Based on the random allocation of individual adult patients with reduced ejection fraction (HFrEF) and left ventricular ejection fraction <45% within the past five years, the caregiver of patients was allocated to receive the REACH-HF intervention over 12 weeks (REACH-HF group) or not (control group). Caregiver outcomes were generic health-related quality of life (EQ-5D-5L), Family Caregiver Quality of Life Scale questionnaire (FamQol), Caregiver Burden Questionnaire HF (CBQ-HF), Caregiver Contribution to Self-care of HF Index questionnaire (CC-SCHFI) and Hospital Anxiety and Depression Scale (HADS). Outcomes were compared between groups at 4, 6 and 12 months follow-up. Twenty caregivers receiving REACH-HF were purposively selected for qualitative interviews at 4 and 12 months. Results: Compared with controls (44 caregivers), the REACH-HF group (53 caregivers) had a higher mean CC-SCHFI confidence score at 12 months (57.5 vs 62.8, adjusted mean difference: 9.3, 95% confidence interval: 1.8–16.8, p = 0.016). No significant between group differences were seen in other caregiver outcomes. Qualitative interviews showed that most caregivers who received the REACH-HF intervention made positive changes to how they supported the HF patient they were caring for, and perceived that they had increased their confidence in the caregiver role over time. Conclusion: Provision of the REACH-HF intervention for caregivers of HF patients improved their confidence of self-management and was perceived for some to be helpful in supporting their caregiver role.